RESTORATION OF DETAILS BY SURFACE PLASTIC DEFORMATION - Dudnikov, A. A.; Dudnyk, V. V.; Burlaka, O. A.; Kanivets, O. V.; Kryvonos, S. M. (Scientific Progress & Innovations, 2020)
A study was conducted as to the effect of strengthening treatment in the restoration of farm machinery details operating under the conditions of increased abrasive wear. The analysis of existing ways of their restoration was made, and the substantiation of using vibration strengthening treatment in repair production was given. The assessment of reliability of grain seeders’ working parts was conducted, taking into account the conditions of their operation, based on mathematical dependencies. Research was carried out to select the optimal parameters of vibration strengthening of seeders’ working parts. Microstructural studies were conducted to determine the effect of the treatment method of sowing boot disk material. Rig tests of sowing boot discs were carried out on installation, which would make it possible to regulate the intensity of disc wear. The values and distribution of residual tensions in the material of a new disc and restored one by the method of welding steel 45 segments with sormite overlaying and vibration strengthening were determined. The values of strengthening degree of the cutting edge material of the restored sowing boot discs were determined. The optimal modes of vibration strengthening were established. The optimal parameters of sowing boot discs were determined: the outer diameter, the thickness of the cutting edge, the angle of the blade, which ensure their least wear and the proper quality of sowing grain crops. The results of changing the disk thickness and its wear along its diameter during rig tests of new discs and those restored by welding steel 45 segments with automatic sormite overlaying and vibration strengthening were presented. Operational studies of the above mentioned variants of grain seeders were carried out in order to check the maintenance reliability of restored and vibration-strengthened sowing boot discs. It has been established that the greatest value of operating time had a seeder with sowing boot discs restored by welding steel 45 segments with subsequent automatic sormite overlaying and strengthened by vibration deformation.